Validation of a modified algometer to measure nociceptive thresholds in awake dogs - Kaka, Ubedullah; Hui, Cheng Chen; Yong, Meng Goh; Abdul Abubakar, Adamu; Fakurazi, Sharida; Ebrahimi, Mahdi (Hindawi Publishing Corporation, 2015)
This study was conducted to validate the use of a modified algometer device to measure mechanical nociceptive thresholds in six dogs. Dogs were administered morphine intravenously (IV) at 1 mg/kg or saline at equivolume in a crossover design with one-week washout period. Mechanical nociceptive thresholds were determined before, after the administration of treatments at 5 minutes, and hourly for 8 hours. Thresholds were recorded at the carpal pad, metacarpal foot pad, tibia, femur, and abdomen. Heart rates, body temperature, and respiration were recorded at similar time points. Thresholds increased significantly (